Մարաղայի բարբառի խոսվածքներ Նախիջևանի տարածքում - Վարդանյան, Արտակ (ՀՀ ԳԱԱ ԼԻ հրատարակչություն)
The article is devoted to a comparison of the dialectal characteristics of the Maragha dialect with the general dialect of the residents who moved to the villages of Verin Aza, Nerkin Aza, Der Gokhtn province of Nakhijevan in the first half of the 19th century from the Maragha region of Persia. The study shows that the mother dialect was largely preserved in the new environment. The phonetic system underwent partial changes (simplification of diphthongs, replacement of palatal գ', կ', ք' with affricates ջ, ճ, չ, absence of sound ւ, etc.). The dialect's declension and conjugation systems basically correspond to the corresponding systems of the Maragha dialect, with few peculiarities. The vocabulary of the mother dialect has also been preserved in its immaculate form, with a limited number of differences. It can be concluded that among the eight dialects on the territory of Nakhijevan, until the second half of the last century, the dialects of the Maragha dialect, with minor phonetic, morphological and lexical features, were also preserved and used. Статья посвящена сравнению диалектных признаков Марагинского диалекта с общим говором жителей, переселившихся в села Верин Аза, Неркин Аза, Дер Гохтнской провинции Нахиджевана в первой половине XIX веке из Марагинской области Персии. Исследование показывает, что мать-диалект в основном сохранился в новой среде. Частичному изменению подверглась фонетическая система (упрощение дифтонгов, замена палатальными գ', կ', ք' на аффрикаты ջ, ճ, չ, отсутствие звука ւ и т. д.). Системы склонения и спряжения говора в основном соответствуют соответствующим системам Марагинского диалекта, с малочисленными особенностями. Лексика мать-диалекта также сохранилась в беспорочном виде, с ограниченным числом различий. Можно сделать вывод, что среди восьми диалектов на территории Нахиджевана до второй половины прошлого века сохранялись и употреблялись также говоры Марагинского диалекта, с незначительными фонетическими, морфологическими и лексическими особенностями.
Keywords: Բարբառագիտություն